Problematika Kebijakan Food Estate Terkait Pemanfaatan Kawasan Hutan Lindung - Salma Jane Benedicta; Rahayu Subekti (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The government is working on a food barn program or commonly referred to as a food estate to anticipate the post-pandemic food crisis. This food estate program is carried out by expanding land including protected forest areas. This raises problems regarding the government's policy in food estate programs that use protected forest areas. The aim of this research is to find out problems in food estate policies related to the use of protected forest areas. This research uses normative research methods, with deduction analysis techniques. The results of this research show that the Food Estate policy has problems related to protected forest areas that can be used for food estate projects which are regulated in Minister of Environment and Forestry Regulation No. 7 of 2021, contrary to Article 26 of Law no. 41 of 1999 which does not include the food estate program in the use of protected forests. This shows that the food estate policy needs to be reviewed, especially regarding the criteria for protected forest areas that do not have a protective function so that there is no conflict between one policy and another.